KEADAAN USAHA TANI SAYURAN DATARAN RENDAH DI KABUPATEN KAMPAR - Rachmiwati Yusuf (Jurnal Sagu, 2010)
Tbe research was conducted at Aur Sati VUiage, Tunbang sub district, Kanspar District, Trom May toNovember 20O7, using survey method. Tbe aim of this research were to get information about condition offarming system and to identify marketing potential of low land vegetables with high productkin and goodmarketing potential. Result of research showed thattowland type vegetable with the highest production blong bean and encumber, but tiie one with best marketing potential b spinach. Spinach had highest sellingpercentage eventhough the one with highest profit percentage was long bean.